Statistics and its importance in validating research findings - Daoud, Jamal Ibrahim (2014)
Researches in life constitute a chain where every ring of it should be verified and validated. Statistics and its tools are widely used in researches regardless to the area of application. Nowadays, we can hardly find any research work without using statistical packages or tool to reach a result and interpret them. The objective of this paper is to touch on a serious problem in validating the research findings. This problem is, in fact, when using statistics and its tool without enough knowledge of how a certain statistical process is working and its requirements, which will result in wrong interpretation, and consequently affecting the validity of the obtained results. The danger comes when these results are used by other researchers as verified and validated facts to build on. This means that, any not validated result will break the chain of research and results in what is called broken link. It is almost impossible to have an exact or approximate statistics on research works that have not been validated due to various reasons. Most serious concern is when these (wrong) findings used by other researchers to conduct new researches. We are trying to give some humble guidelines to avoid or minimize broken links in researches.